Exploration of the Semiotics of The Meaning of Javanese Cultural Traditions on “Maghrib Time” Horror Movie Poster - Rd. Dancu Lokita Pramesti Dewi; Umaimah Wahid; Frengky Napitupulu (Jurnal Edusci, 2026)
Background. The prohibition of leaving the house at sunset is believed to be a myth passed down from generation to generation. A myth is a story set in the past, contains an interpretation of the universe, and is considered to have happened by the person who tells the story or its adherents. Then, in a broader sense, a myth can refer to a traditional story. The film poster Maghrib Time is related to the myth of the prohibition on leaving the house during Maghrib etiquette. Then there are visual signs, such as child visuals, cultural elements, and characteristic design elements, including colour, layout, images, logos, and typography. Aims. This research aims to examine the meanings of Javanese cultural traditions on Maghrib film posters and the meanings of the signs. Methods. Then, the data sources were obtained from two sources: primary (observations on film posters at Maghrib time) and secondary (documentation such as interviews, the internet, journals, and books), using qualitative methods and Charles Sanders Peirce's semiotic analysis approach, based on object, representation, and interpretant. Data were obtained from observations, interviews, and a literature review. Result. The results of this research are that, in Maghrib Time, many supernatural creatures roam around, so it is recommended that children not go out at that time. It is also believed in the myth that at dusk, there is a new gimbal figure who likes children in the dark. There are also icons, indexes, and symbols through the selection of typographic elements, images, and colours.